Robust stabilization of state delayed discrete-time Takagi-Sugeno fuzzy systems with input saturation via an anti-windup fuzzy design - 宋晓娜 付主木 刘磊坡 (Chinese physics B, 2012)
We consider the robust stabilization problem for discrete-time Takagi-Sugeno （T S） fuzzy systems with time- varied delays subjected to input saturation. We design static and dynamic anti-windup fuzzy controllers to ensure the convergence of all admissible initial states within the domain of attraction. Based on the project lemma and classical sector conditions, the conditions for the existence of solutions to this problem are obtained and expressed in terms of a set of linear matrix inequalities. Finally, a numerical example is provided to illustrate the effectiveness of the proposed design approach.